Notes on acetes shrimp’s landing status in Malaysia associated with morphometric characterization and genetic identification - Stephenie Demie Anak Kawi (2023)
Acetes are tiny planktonic shrimps, which the locals refer as "Udang Baring" or "Bubuk" in their dialect. Studies on Acetes shrimps have primarily been conducted in Peninsular Malaysia and Sarawak and have focused on the distribution, diet composition, population, morphometric data, and genetic variation. Even though these shrimps are economically significant for human consumption and the aquaculture industry, there has only been a very limited amount of research done on this genus in Sabah waters. Understanding the population structure and genetic information is essential for managing and evaluating wild stock populations. In this study, the Department of Fisheries Malaysia's annual published landing data from nine Malaysian states—Perlis, Kedah, Pulau Pinang, Perak, Selangor, Melaka, Johor (West Johor and East Johor), Sarawak, and Sabah—were used to assess the landing status of Acetes. Overall, the findings indicated that annual landings have increased over the past 26 years, reaching a peak of 52569.00 tonnes in 2010. According to the data from the Department of Fisheries Malaysia, there has been a considerable decline in Acetes population landings during the previous few years in Malaysia. Overexploitation may have resulted from yields that were higher than the 900 000 tonnes which was considered to be the optimal yield. Additionally, Acetes species were gathered from the fishermen in four different Sabah water locations. Based on the identification keys provided by Omori (1975b), three species—Acetes australis, Acetes erythraeus, and Acetes intermedius—had been captured and recognised. For each species, measurements of the carapace length (CL), telson length (TLL), total length (TL), and wet weight (WW) were taken from 885 specimens and compared between species and sexes. A. intermedius is the largest of the three species, whereas A. australis has the lowest measurement and is often smaller than A. erythraeus and A. intermedius. Length-weight relationship observed was significantly high (P=0.05) except for females A. erythraeus (P=0.403). With the help of the mitochondrial cytochrome c oxidase subunit I (COI) gene, the three species were identified, evidenced by both morphological and molecular aspects. These species' average sequence divergence ranged from 7.20%—19.46%. Moreover, high bootstrap values consistently showed three monophyletic different clades based on phylogenetic trees constructed using Maximum Likelihood and Bayesian Inference with the aligned COI gene, which are in agreement with the stated species. In conclusion, despite the possibility of overexploitation in some Malaysian states, the rising trend in Acetes landings demonstrated that the industry is receiving greater attention. The number of Acetes species in Malaysian seas had been increased to eight species, after the recent identification of three species in Sabah waters.